SO_GERICHTE ZZ.1997.14 vom 19. November 1997 , Keine Begünstigung durch Beherbergen des straffälligen Ehegatten - SO Obergericht (1997)
Art. 305 StGB. Keine Begünstigung durch Beherbergen des straffälligen Ehegatten.